Solidification of the eutectic Ga–Sn alloy - Aleksandrov, V.D.; Frolova, S.A.; Amerkhanova, Sh.K. (Pleiades Publishing, 2016)
Cyclic thermal analysis is used to study the effect of overheating of the eutectic Ga–8.5 mol % Sn melt on the presolidification supercooling. It is found that, when the liquid eutectic is overheated above the eutectic temperature (T e = 293.5 K) and is subsequently cooled, the dependence of the presolidification supercooling on the overheating temperature exhibits monotonic ascending behavior. The maximum supercooling after heating of the melt to 339 K is 26 K. The kinetic and thermodynamic parameters of eutectic solidification are calculated using the thermal analysis curves measured during melting.